ASSESSMENT OF FISH STRUCTURE COMMUNITY AT GREATER ZAB RIVER NEAR ASKI-KALAK CITY,ERBIL - Safeen.O. S.; S. M. A. Abdulla (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The structure of fish community was evaluated before and after Aski-Kalak City at Greater Zab River, Erbil Province, Iraq during the period from November 2020 to October 2021. A total of 1582 specimens belonged to 25 fish species were collected and reached to 570 Kg of total weights. These fish were mostly belonging to Cyprinidae family and one for each Mugilidae, Siluridae, Bargridae, Sisoridae and Mastacembelidae. According to fish occurrence in (S1), there were five fish species be as resident, 8 and 10 species as seasonal and rare respectively. The annual values of fish species, weight and catches effort 10.7, 184 and 33.25 Kg/hour respectively, and in (S2) fish species of 6, 6 and 11 as resident, seasonal and rare respectively.The annual values of fish species, its weight and catches were 10.7, 210 and 38.59 Kg/hour respectively. The present study concluded that section of Greater Zab River (S2) was suitable for fish composition more than(S1).